2020
DOI: 10.1021/acs.jpclett.0c01937
|View full text |Cite
|
Sign up to set email alerts
|

Transport Mechanisms Underlying Ionic Conductivity in Nanoparticle-Based Single-Ion Electrolytes

Abstract: Recent studies have demonstrated the potential of nanoparticle-based single-ion conductors as battery electrolytes. In this work, we introduce a coarse-grained multiscale simulation approach to identify the mechanisms underlying the ion mobilities in such systems and to clarify the influence of key design parameters on conductivity. Our results suggest that for the experimentally studied electrolyte systems, the dominant pathway for cation transport is along the surface of nanoparticles, in the vicinity of nan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…For example, more recently, a similar method has been applied to study ion transport in nanoparticle-based single-ion conductors. 115 Other dimensions in the design space of salt-doped polymers were explored by our group with a different approach to consider the strong ion to polymer interactions on a coarse-grained level. 54,116,117 Specifically, our CG model contains a 1/r 4 potential form, the same as that of an ion to an induced dipole, to generically represent ion size and dielectric dependent ion solvation.…”
Section: Homopolymer Electrolytesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, more recently, a similar method has been applied to study ion transport in nanoparticle-based single-ion conductors. 115 Other dimensions in the design space of salt-doped polymers were explored by our group with a different approach to consider the strong ion to polymer interactions on a coarse-grained level. 54,116,117 Specifically, our CG model contains a 1/r 4 potential form, the same as that of an ion to an induced dipole, to generically represent ion size and dielectric dependent ion solvation.…”
Section: Homopolymer Electrolytesmentioning
confidence: 99%
“…They showed that as the polarity increases, a competition between better ion dissociation (smaller ion clusters and improved degree of uncorrelated ion motion) and slowed polymer dynamics arises, causing a nonmonotonic trend in total conductivity. , Such a CG simulation approach can be easily applied to other ion-containing polymer systems of interest. For example, more recently, a similar method has been applied to study ion transport in nanoparticle-based single-ion conductors …”
Section: Recent Applications and Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 30 ] This is because the aggregation‐induced gelation effect of the porous LiF nanobox results in largely enhanced macroscopic viscosity but has a little influence on the microscopic viscosity of the prepared electrolyte. In the nanoparticle‐based electrolyte, [ 31 ] the microscopic viscosity is the dominant parameter to determine the ion diffusion coefficient according to the Stokes‐Einstein equation and further correlate to the ionic conductivity based on the Nernst‐Einstein equation. Therefore, the ion diffusion coefficient and ionic conductivity in our porous LiF nanobox based electrolyte are not greatly influenced by the concentration of porous LiF nanoboxes as that of the tested macroscopic viscosity (Note S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we demonstrate the above strategy by the application of deep learning approaches for predicting the diffusion coefficient of cations in single-ion conducting nanoparticle-based electrolytes. The choice of the system was inspired by a recent study of ours probing the mechanistic bases for ion transport observations reported in these electrolytes. Our results in such a context were consistent with the reported experimental behavior of electrolytes comprising silica nanoparticles, cofunctionalized with poly­(ethylene glycol) ligands and tethered anionic species coupled to Li + ions, dispersed in ion-conducting tetraglyme solvent. , Our simulation results suggested that ionic conductivity in such systems is primarily controlled by cation diffusion along functionalized nanoparticle surfaces.…”
Section: Introductionmentioning
confidence: 99%